Spectrophotometric Determination of Sildenafil in Tablets - Vidya Sagar, G. (Asian Journal of Chemistry, 2016)
Two simple and sensitive spectrophotometric methods for the determination of sildenafil in bulk and pharmaceutical dosage forms are described. The methods involve formation of charge transfer complexes of the drug with chloranilic acid (method A) and chloranil (method B). The absorption maxima and Beer's law linearity range for method A are 430 nm. 10–60 μg/mL and for method B are 540 nm, 20–120 μg/mL respectively. When pharmaceutical preparations containing sildenafil (tablets) were analysed, the results obtained by the proposed methods are in good agreement with the labelled amounts. Recovery is 98–101%.